Experimental investigation to enhancing the energy efficiency of a solar-powered Visi cooler - K. Senthil Kumar; R. Vasanthi; Mustafa Shakir; Arunkumar Munimathan; A. S. Manirathnam; Mohammad Mukhtar Alam; Parvathy Rajendran; It Ee Lee (Scientific Reports)
Abstract Refrigeration methods in secluded regions are a major issue for sustaining the quality of perishables like vaccines and food. Traditional refrigeration systems, including kerosene and gas-powered units, often suffer from interruptions in the supply of fuel. Additionally, they do not satisfy the stringent criteria set by the World Health Organization (WHO) Performance, Quality and Safety (PQS) system requirements. While solar-powered refrigeration is an alternative, existing systems heavily rely on battery storage, which increases maintenance, costs, and limits system lifespan. This study analyses the operational efficiency of a solar-powered VISI cooler with a DC compressor-based refrigeration system, adding and omitting phase change materials (PCM). The experimental findings demonstrate that incorporating PCM significantly enhances energy efficiency by reducing average power consumption from 48 to 40 W. This decreased power consumption increases suction pressure by 0.13 bar and decreases compressor output pressure by 0.76 bar. These improvements aid in optimised thermal regulation which lowers dependency on conventional energy storage methods. The research indicates the role of collaborative partnerships between governments, research bodies, and technology developers aimed at fostering sustainable and innovative peak-shaving refrigeration solutions geared towards off-grid systems.